Kompensasi dan Kepuasan Kerja Dalam Meningkatkan Kinerja Karyawan - Tia Siti Khodijah; Yelsha Dwi Pasca (Papanda Publisher, 2023)
Human resources are considered as an asset for companies with high employee performance which can be influenced by compensation and job satisfaction. This study aims to determine how much influence compensation and job satisfaction have on performance at Surya Jatiwangi Department Store in Majalengka Regency, either partially or simultaneously. The research method used is descriptive and verification method with a total sample of 92 respondents. Data collection techniques used were documentation, observation, interviews and distributing questionnaires. The results of the research show that compensation, job satisfaction and employee performance at Surya Jatiwangi Department Store in Majalengka Regency can be said to be good. The research data shows that partially, compensation has a positive and significant influence on employee performance. The same results also show that job satisfaction has a positive and significant effect on employee performance. Simultaneously, compensation and job satisfaction also have a significant effect on the performance of Jatiwangi Surya Department Store employees. The conclusion of this study is that compensation and job satisfaction can improve employee performance,